The Induction of IgM and IgG Antibodies against HLA or MICA after Lung Transplantation - Annelieke W. M. Paantjens; Ed A. van de Graaf; Johanna M. Kwakkel-van Erp; Tineke Hoefnagel; Walter G. J. van Ginkel; Farzia Fakhry; Diana A. van Kessel; Jules M. M. van den Bosch; Henny G. Otten (Pulmonary Medicine)
The production of IgG HLA antibodies after lung transplantation (LTx) is considered to be a major risk factor for the development of chronic rejection, represented by the bronchiolitis obliterans syndrome (BOS). It has recently been observed that elevated levels of IgM HLA antibodies also correlates with the development of chronic rejection in heart and kidney transplantation. This study investigates the relationship between IgM and IgG antibodies against HLA and MICA after lung transplantation. Serum was collected from 49 patients once prior to transplantation and monthly for up to 1 year after lung transplantation was analyzed by Luminex to detect IgM and IgG antibodies against HLA and MICA. The presence of either IgM or IgG HLA and/or MICA antibodies prior to or after transplantation was not related to survival, gender, primary disease, or the development of BOS. Additionally, the production of IgG alloantibodies was not preceded by an increase in levels of IgM, and IgM levels were not followed by an increase in IgG. Under current immune suppressive regimen, although the presence of IgM antibodies does not correlate with BOS after LTx, IgM high IgG low HLA class I antibody titers were observed more in patients with BOS compared to patients without BOS.